Symposium: Laparoscopy, up-to-date - Celis L, Alfredo (2015)
"Why look through the keyhole when you can open the door?" .... This was the disparaging remark of an eminent gynecologist after the presentation of some of the first observations made by one of the pioneers of laparoscopy in the last century; and probably still remains the thinking of many, but I think increasingly colleagues regarding this surgical technique.